Study of hard core repulsive interactions in an hadronic gas from a comparison with lattice QCD. (August 2016) - Alba, P; Vovchenko, V; Stoecker, H
Abstract: We study the influence of hard-core repulsive interactions within the Hadron- Resonace Gas model in comparison to first principle calculation performed on a lattice. We check the effect of a bag-like parametrization for particle eigenvolume on flavor correlators, looking for an extension of the agreement with lattice simulations up to higher temperatures, as was yet pointed out in an analysis of hadron yields measured by the ALICE experiment. Hints for a flavor depending eigenvolume are present.